Factor structure of postconventional moral consciousness of the students - Tymosh, Yuliya (Psychological Prospects Journal, 2017)
The article presents the results of factor analysis of the postconventional stage of moral consciousness of student youth at different levels. It was investigated that the factor structure of a high-level postconventional moral consciousness reflects the individual intention to define universal moral values that are autonomous from a concrete situation and concrete people involved in this situation. The internal system of human principles is oriented on a social agreement, conditioned by the officially accepted social morality. This is well correlated with high normativity as a person’s orientations to follow social norms and rules, and with sociability and diplomacy as a focus on respect for human-rights arrangements. Autonomous human morality, determined by the universal ethical principles of justice, goodness, faith, beauty, is supported by altruistic emotions, existential responsibility, and the combination of intelligence and intuition as a rational and intuitive-sensory reflection of reality. It was also determined that individuals with an average level of postconventional moral consciousness are less dynamic compared with the low level, are distinguished by greater consistency and weight in the development of moral consciousness. The results of the analysis of the factor structure of the low level of postconventional consciousness indicate that it contains the following characteristics: the internal system of human principles, oriented to a social agreement, conditioned by the officially accepted social morality, high social orientation, along with elements of suspicion, radicalism, if it contradicts its own needs. This, in our opinion, is determined by the greater manifestations of preconventional moral consciousness in the low level of postconventional consciousness in comparison with the middle and high levels.